The adhesion of alumina films to metallic alloys and coatings - (:unkn) unknown (WILEY-V C H VERLAG GMBH, 2000)
The adherence of protective oxide scales to alloy substrates is governed by the stored elastic energy in the scale which drives delamination and the fracture resistance of the alloy oxide interface. Clearly any modifications to the alloy or the exposure environment which decreases the former or increases the latter will improve the durability of a given system. The stored elastic energy is determined by the stress level in the scale and the scale thickness. The stress state in the scale is determined by stresses which arise during the oxide formation (Growth Stresses). stresses produced during temperature changes as the re suit of thermal expansion mismatch between the oxide and the alloy (Thermal Stresses), and any stress relaxation which occurs as the result of creep of the scale or alloy. The fracture energy of the interface is a function of the composition at the interface, the microstructure in the interfacial region, and the composition of the exposure environment. This paper focuses on the results of studies of a variety of alloys and coatings. all of which form continuous alumina scales, in which it has been attempted to evaluate the effects of various alloy and exposure parameters on the stress state in the scale, the microstructure of the alloy/oxide interface, and the fracture resistance of the interface. The alloy parameters include alloy type, sulfur content, and reactive element content. The exposure parameters include oxidation temperature, temperature profile during exposure, and water vapor and sulfur contents of the atmosphere.
Keywords: OXIDE SCALE ADHERENCE; CR-AL ALLOYS; REACTIVE-ELEMENT; OXIDATION RESISTANCE; SINGLE-CRYSTALS; SULFUR REMOVAL; THIN-FILMS; SEGREGATION; INTERFACE; GROWTH